Roy’s Adaptation Model and the Dual Process Model of Grieving substantiating palliative nursing care to the family - Araujo da Silva, Vladimir; Frederico Silva, Rita de Cássia; Martins Trovo, Monica; Paes da Silva, Maria Júlia (O Mundo da Saúde, 2017)
One of the principles of palliative care is to assist in identifying and mobilizing a support system to help the family deal with the patient’s illness and his or her own grief. In this perspective, the objective of this study was to propose a reflection about palliative nursing care given to the bereaved family, based on the theory of Roy’s Adaptation Model and the Dual Process Model of Grief. It is a theoretical-reflexive study based on the philosophical principles of palliative care, especially Roy’s Adaptation Model and its intersection with the Dual Process Model of Grief. This theoretical reflection shows that grief is a focal stimulus directly confronted by the family, which can be manipulated by the nurse’s compassionate presence and by active and welcoming listening during the elaboration process, helping the family in the process of reorganizing life and adapting changes resulting from loss, reducing inefficient responses. We suggest the use of Roy’s Adaptation Model and the Dual Process Model of Grief as theoretical references for nurses’ palliative care given to the bereaved family.